Enhanced Iron Flux to Antarctic Sea Ice via Dust Deposition From Ice‐Free Coastal Areas. Issue 12 (4th December 2019) - Duprat, L.; Kanna, N.; Janssens, J.; Roukaerts, A.; Deman, F.; Townsend, A. T.; Meiners, K. M.; van der Merwe, P.; Lannuzel, D.
Abstract: Antarctic sea ice is an important temporal reservoir of iron which can boost primary production in the marginal ice zone during the seasonal melt. While studies have reported that Antarctic fast ice bears high concentrations of iron due to the proximity to coastal sources, less clear are the biogeochemical changes this iron pool undergoes during late spring. Here we describe a 3‐week time series of physical and biogeochemical data, including iron, from first‐year coastal fast ice sampled near Davis Station (Prydz Bay, East Antarctica) during late austral spring 2015. Our study shows that dissolved and particulate iron concentrations in sea ice were up to two orders of magnitude higher than in under‐ice seawater. Furthermore, our results indicate a significant contribution of lithogenic iron from the Vestfold Hills (as deduced from the comparison with crustal element ratios) to the particulate iron pool in fast ice after a blizzard event halfway through the time series. Windblown dust represented approximately 75% of the particulate iron found in the ice and is a potential candidate for keeping concentrations of soluble iron stable during our observations. These results suggest that iron entrapped during ice formation, likely from sediments, as well as local input of coastal dust, supports primary productivity in Davis fast ice. As ice‐free land areas are likely to expand over the course of the century, this work highlights the need to quantify iron inputs from continental Antarctic dust and its bioavailability for ice algae and phytoplankton. Plain Language Summary: Oceanic single‐celled algae are the base of the ocean food web and play an important role in the Earth climate. In the Southern Ocean, the growth of these microorganisms is limited by the naturally low concentration of iron in the seawater. Microalgae benefit from the presence of the Antarctic sea ice since iron is highly concentrated in sea ice relative to the seawater. Less clear though is the contribution of the potential sources of iron to the sea ice. We collected and analyzed sea ice cores for a series of parameters, including iron, from first‐year coastal sea ice sampled near Davis Station (Prydz Bay, East Antarctica) during late austral spring 2015. Our results suggest that iron entrapped during ice formation, likely from seafloor sediments, as well as dust blown by winds from the neighboring Vestfold Hills, are the main sources of iron to Davis coastal sea ice. Since we can expect the expansion of ice‐free areas and exposed grounds over the course of this century, our results highlight the need to quantify the amount of iron coming from continental Antarctic dust and to access if microalgae can use this form of iron for their basic physiological needs. Key Points: Primary production in East Antarctic fast ice is not Fe‐limited during late spring/early summer Iron in suspended sediment entrapped during ice formation supports primary production in the ice Windblown dust from ice‐free coastal landmasses in the Vestfold Hills contributes significantly to the total iron pool in Davis fast ice